1988
DOI: 10.1007/bf00379604
|View full text |Cite
|
Sign up to set email alerts
|

The role of fish in distribution and germination of seeds of the submerged macrophytes Najas marina L. and Ruppia maritima L.

Abstract: The effects of three species of fish (tilapia, grass carp and common carp) on the seeds of Najas marina L. and of Ruppia maritima L. were investigated. Practically all the seeds that were injested by the common carp were digested. The two other fish were less affective: they digested seeds with soft seed-coats but excreted a good portion of the hard ones. Germination of the excreted seeds was improved. Seeds have been retained in the digestion tracts of the fish for up to 65 h. It is thus suggested that tilapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 22 publications
3
61
0
Order By: Relevance
“…For example, seeds of Nuphar lutea, Nymphea alba and Nymphoides peltata are often eaten by breams, ides roachs, carps and rudds (Agami & Waisel 1988;Cook 1990b;Smits et al 1989;Van der Pijl 1972) and Lemnaceae are one of the most important components in the diet of the muskrat (Jacobs 1947). However, little information exists about the viability of the propagules that have passed through the digestive tracts of these animals.…”
Section: Animal Dispersionmentioning
confidence: 99%
“…For example, seeds of Nuphar lutea, Nymphea alba and Nymphoides peltata are often eaten by breams, ides roachs, carps and rudds (Agami & Waisel 1988;Cook 1990b;Smits et al 1989;Van der Pijl 1972) and Lemnaceae are one of the most important components in the diet of the muskrat (Jacobs 1947). However, little information exists about the viability of the propagules that have passed through the digestive tracts of these animals.…”
Section: Animal Dispersionmentioning
confidence: 99%
“…Seed retention time in fishes is long compared with that of other vertebrate dispersers. For instance, Pollux and colleagues (2006) found that 50% of the seeds consumed by common carp were excreted approximately 7 hours later; Agami and Waisel (1988) found that the same proportion of seeds were excreted approximately 40 hours after ingestion by tilapia and grass carp; and Horn (1997) reported that approximately 30% of seeds were excreted at 24 hours, 84% at 36 hours, and 88% at 48 hours by B. guatemalensis. In contrast, seed retention time is generally less than one hour in bats (Shilton et al 1999) and passerine birds (Levey 1986).…”
Section: Fishes As Seed Dispersersmentioning
confidence: 99%
“…Piaractus brachypomus (Serrasalmidae), a specialized frugivore from the Amazon and Orinoco basins, recently became established in the Sepik River in Papua New Guinea (Coates 1997) and now provides an important fishery resource (figure 1e). Grass carp (Ctenopharyngodon idella [Cyprinidae]) that were introduced into reservoirs in Israel enhanced the seed germination of two native aquatic plants, Najas marina (Najadaceae) and Ruppia maritima (Potamogetonaceae); given their longitudinal and lateral migrations in river systems, Ct. idella may be able to disperse seeds over long distances (Agami and Waisel 1988).…”
Section: Prospects For the Study Of Ichthyochory And Conservation Impmentioning
confidence: 99%
“…They quickly reach sexual maturity and produce large amounts of seeds (Bonis et al 1995). In the case of R. maritima, these seeds can remain dormant for extended periods of time (Kantrud 1991) and are able to survive passage through the digestive system of waterfowl and fish, which favors long-distance dispersal of the plants (Agami & Waisel 1988, Charalambidou et al 2003.…”
Section: Introductionmentioning
confidence: 99%